(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: This review presents the report of the research group at the police headquarters of North Rhine-Westphalia, published in 2015. The authors have analysed forensics-criminology data from files of all known infanticides between 1990-2007 (two missing) in all states of Germany using statistical methods. Methodology: The authors of the reviewed article present characteristics of the act, the perpetrator and the victim from the semantic viewpoint of criminology, thus this review aims follow their arguments as close as possible to make the review as useful as possible. Findings: The database the authors have created provide well-founded data on probabilities to characterise both the perpetrator and the act. Value: There are only few who attempt a forensics-criminology analysis of the whole universe of criminal acts against newborns over the span of a longer period. The conclusions drawn using the database and methods the authors created help strategic planning of the investigation as well as the choice of tactical elements. It is worth therefore considering a similar approach when analysing further the database of similar cases in Hungary, spanning almost 40 years.